Pressure, droplet size classification, and nozzle arrangement effects on coverage and droplet number density using air-inclusion dual fan nozzles for pesticide applications. (November 2016) - Ferguson, J. Connor; Hewitt, Andrew J.; O'Donnell, Chris C.
Abstract: Spray applications are most effective when they cover the greatest per unit area, improving target pest control. In order to optimize spray applications, nozzle companies have developed new designs that seek to provide the greatest and most uniform coverage per target unit area. While dual fan nozzles have been examined against single fan nozzles in several studies, there has not been a comprehensive comparison of multiple nominal flow rate and multiple dual fan nozzle types. This study sought to examine pressure, droplet size classification, and nozzle arrangement effects on droplet number density on horizontal artificial collectors using a fixed application rate. The relationship between coverage and nozzle type was significant (P < 0.001) as was the relationship between coverage and pressure (P < 0.001). The 207 kPa pressure resulted in the highest coverage for every nozzle type except the alternating TADFs (ATADF)s. The GAT 11003 resulted in the highest coverage overall with 39.6% at the 207 kPa pressure, followed by the TADF 11005 and TADF 11003 at 38.6% and 38.3% coverage respectively. The effect of pressure was significant for the droplet number density (P < 0.001) as was the effect on droplet number density from nozzle type (P < 0.001). The 414 kPa pressure resulted in the highest droplet number density for all nozzle types except the AITTJ 11003 and the MDD 11004. The GAT 11003 and GAT 11004 produced the highest overall droplet number densities with 73.0 and 72.6 droplets cm 2 at the 414 kPa pressure. The GAT 11003 had the greatest droplet number density at every pressure. Nozzle arrangement has a significant effect on spray coverage with asymmetric dual fan nozzles, and it would be recommended to alternate these nozzles on a spray boom to increase coverage especially at higher application speeds. Results from this study show that an applicator can select a coarser droplet size classification without observable loss in coverage, while greatly reducing the drift potential of the application. Highlights: Pressure affected coverage - 207 kPa resulted in highest coverage for every nozzle. Alternating TADF nozzles reduced the negative effect of speed on collector coverage. The Guardian Air Twin 11003 had the highest coverage and droplets cm −2 . Nozzle flow rate did not affect coverage across nozzle type. A coarser droplet size spray can be used without observable loss in coverage.